Corporate governance and audit lag in Nigerian quoted companies - Beri, Mohammed Haliru (2015)
Unnecessary audit lag or delay decreases the quality or superiority of the financial report by not allowing investors and stakeholders to have appropriate information about their investment. The audited Financial Statements are important instrument for decision making purposes. However, before it can be released to the public, it must be examined by the auditor. Thus, the speed of Financial Statements production is subject to the completion of audit work. The purpose of this study is to investigate the audit lag (i.e. time taken to complete the audit work) of Nigerian quoted companies, as listed on the Nigerian Stock Exchange for the period of 2012 to 2013. The examination was conducted on a pooled sample of 266 firm-years across ten industries. Data collected was analysed by the regression method and the results from the analysis show that, on average, Nigerian auditors spend 132 days to complete the audit work. The time taken is more than the time allowed for the submission of the annual return to the Nigerian Stock Exchange, i.e. 120 days. Firm size, leverage and profitability were established to be significant in explaining the audit lag. It is argued that bigger companies, in order to maintain investors’ confidence, would make their Financial Statements ready for audit earlier than smaller companies. In addition, since these companies also have better internal control, it is relative easier for their auditors to complete the audit field work. However, companies with more leverage and profitably were found to subject to longer audit work. This is perhaps due to auditors’ doubtful about the reported accounts since fraudulent reporting is not unusual in Nigeria. The following recommendations are suggested. The release of businesses’ financial report ought to be done appropriately, hence that will enable the shareholders to make the right investments decision. The supervisory agencies (e.g. SEC, NSE, CAMA) should formulate a strict and rigid polices that will force the companies to comply with the timely release of audited accounts